Development of Integrated TaRL Teaching Materials to Foster Deep Learning in Elementary School - Yantoro; Muhammad Sholeh; Mohamad Muspawi; Ahmad Hariandi; Eka Sastrawati; Sri Marmoah (Jurnal Penelitian Pendidikan IPA, 2025)
This research and development (R&D) study aims to develop and evaluate the validity and practicality of integrated teaching materials based on the Teaching at the Right Level (TaRL) approach with deep learning principles to enhance the mathematical understanding of fourth-grade elementary school students. The study was conducted in response to the challenge of teachers' limited competence in designing teaching tools that are responsive to students' diverse needs and characteristics, a key requirement of Indonesia's Independent Curriculum. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was employed as the systematic development framework. The subjects were students from SDN 131/IV, SDN 42/IV, and SDN 64/IV in Jambi City. Data were collected through validation sheets by experts and practicality questionnaires administered to teachers and students. The results demonstrated that the developed teaching materials achieved a very high validity level, with an average score of 97.36% across media, content, and language aspects. Furthermore, practicality tests showed consistently high scores from both teachers and students across all three schools, with averages above 89%, categorized as "Good Practicality." The findings indicate that the deep learning-based TaRL integrated teaching material is a valid, practical, and effective tool for facilitating personalized, engaging, and collaborative mathematics learning, ultimately supporting the goals of differentiated instruction within the Independent Curriculum.